Circulating N-Terminal Probrain Natriuretic Peptide Levels in Relation to Ischemic Stroke and Its Subtypes: A Mendelian Randomization Study - Li, Ming; Xu, Yi; Wu, Jiaqi; Wu, Chuanjie; Li, Ang; Ji, Xunming (Frontiers in Genetics, 2022)
Mendelian randomization was used to evaluate the potential causal association between N-terminal pro-brain natriuretic peptide (NT-proBNP) and ischemic stroke, based on summary statistics data from large-scale genome-wide association studies. Three single-nucleotide polymorphisms rs198389, rs13107325 and rs11105306 associated with NT-proBNP levels found in large general populations and in patients with acute heart disease were used as instrumental variables. The results of genetic association analysis of each single single-nucleotide polymorphism (SNP) show that there is no significant association between NT-proBNP levels and ischemic stroke or its subtypes, while rs198389 alone has suggestive association with large-artery atherosclerosis stroke (LAS). The MR analysis of 3 SNPs shows that NT-proBNP levels may reduce the risk of small-vessel occlusion stroke suggestively. This genetic analysis provides insights into the pathophysiology and treatment of ischemic stroke.